Overexpressed Nup88 stabilized through interaction with Nup62 promotes NF-κB dependent pathways in cancer - Singh, Usha; Bindra, Divya; Samaiya, Atul; Mishra, Ram Kumar (Frontiers in Oncology, 2023)
Bidirectional nucleo-cytoplasmic transport, regulating several vital cellular processes, is mediated by the Nuclear Pore Complex (NPC) comprising the nucleoporin (Nup) proteins. Nup88, a constituent nucleoporin, is overexpressed in many cancers, and a positive correlation exists between progressive stages of cancer and Nup88 levels. While a significant link of Nup88 overexpression in head and neck cancer exists but mechanistic details of Nup88 roles in tumorigenesis are sparse. Here, we report that Nup88 and Nup62 levels are significantly elevated in head and neck cancer patient samples and cell lines. We demonstrate that the elevated levels of Nup88 or Nup62 impart proliferation and migration advantages to cells. Interestingly, Nup88-Nup62 engage in a strong interaction independent of Nup-glycosylation status and cell-cycle stages. We report that the interaction with Nup62 stabilizes Nup88 by inhibiting the proteasome-mediated degradation of overexpressed Nup88. Overexpressed Nup88 stabilized by interaction with Nup62 can interact with NF-κB (p65) and sequesters p65 partly into nucleus of unstimulated cells. NF-κB targets like Akt, c-myc, IL-6 and BIRC3 promoting proliferation and growth are induced under Nup88 overexpression conditions. Our data indicates that simultaneous overexpression of Nup62 and Nup88 in head and neck cancer stabilizes Nup88. Stabilized Nup88 interacts and activates p65 pathway, which perhaps is the underlying mechanism in Nup88 overexpressing tumors.